Penerapan Metode Haversine Pada Sistem Informasi Geografis Untuk Penentuan Lokasi Pembangunan Menara Telekomunikasi Pada Kota Tangerang - Achmad Maulana; Achmad Solichin; Mohammad Syafrullah (Indonesian Journal on Software Engineering (IJSE), 2018)
Abstract - Development Telecommunication Tower growth cannot be avoided. Accordingly, the local government makes local regulations on Planning and Control of Telecommunication Tower to avoid illegal construction of Telecommunication Tower because makes a reduction in open land and also reduces the aesthetic value of the spatial region. The researcher conducted a study on the implementation of methods haversine on a geographic information system is expected to simplify the process of distance measurements for the determination of Telecommunication Tower towards he elliptical shape of the earth. Keywords: GIS, haversine, RAD, google map